Habitar Sozinho Acompanhado. A transformação da casa da Quinta dos Carvalhiços num espaço inclusivo - Joana Sousa Ferreira (2022)
Living alone together focuses on the adaptation and rehabilitation of Quinta dos Carvalhigos house, an extensive propgrfy both in size and history that is currently forgotten and uninhabitable into an inclusive program. Quinta dos Carvalhigos is located in Sáo Miguel de Outeiro, Tondela district. Due to the drop in births and the exodus ofthe active class, the population reduction over the last few decades is clear. This trend is followed by an increase of the elderly population. The dissertation uses the project as a bridge to, not only answer some of, the existing gaps in the constructions of the past particularly its adequacy to the current demands of domestic comfort, but also to transform the house in an inclusive space, adjusting the spaces to any life phase, focusing, in particular, on ederly peopple. It is not intended that the project has a fixed characte¡ but rather to be moldable by times and wills. The appropriation and adjustment of space is fundamental to life but, to do so, it is also important to recognize the identity of the place that must remain. Programs must adapt to new needs, while preserving the best qualities of the original architecture. The development of the work focuses on the issues ofthis age group - the difficulry in changing address, accessibility, adequate rehabilitation for the elderly and its implications in the program that responds to the aging process. The way in which the House has been adapted to the most diverse programs over time is essential to an understanding of the essence and history of the place. This initial study is crucial for the final proposal to be able to recognize the specificity of the work and adapt it to new needs and demands, both at the regulatory and design levels.